Negotiating in European Union countries - Katz, Lothar (Henry Stewart Talks, 2011)
Process & phases, Negotiation attitudes, Upfront expectations, Bargaining exchange: expected length & attitudes towards haggling, Attitudes towards contracts, Important preparation steps, Specific examples and negotiation hints: Germany, Italy, United Kingdom, France and Spain, Commonalities across Europe